Perkembangan Organisasi Sai Study Group Di Kota Denpasar Tahun 1983-2012. - Anandha Putra, I Gusti Putu; Ardhana, I Ketut; Suwita, I Putu Gede (Humanis; Volume 17. No. 2. Nopember 2016, 2016)
Sai Study Group is a spiritual organization in the form of a study group to study and explore the teachings contained in the Vedic scriptures based on the viewpoint of Bhagawan Sri Sathya Sai Baba. Sai Study Group Organization is a spiritual organization and the largest number of followers in Bali. During its development, the Sai Study Group organization in Bali, especially in Denpasar are many challenges for Sai Study Group organizations because the organization is strayed from tradition and religion of Balinese Hinduism.